Performance of switched-beam element phased array for handset adaptive antenna - Boonpoonga, Akkarat; Sirisuk, Phaophak; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2007)
This paper evaluates the performance of a handset adaptive antenna using a constant modulus algorithm (CMA). The antenna is a switched-beam phased array antenna which can assist initialization of CMA. The method to improve convergence property of CMA exploits a beam with maximum received power from several switched-beams of the antenna as an initial beam. Simulation results in term of signal-to-interference plus noise ratio (SINR) are shown to validate that the proposed antenna has a good performance and is suitable for installation on a handset. © 2007 EuMA.
Keywords: Adaptive antenna; CMA; Initialization; Phased array